Representing Islam: Hip-Hop of the September 11 Generation (by Kamaludeen Mohamed Nasir): Indiana University Press, 2020. xii+206 pages. (American Journal of Islam and Society, 2022)
For the past decades, broad questions as to “what is Islam” and “what does it mean to be Islamic” have haunted much of the fields of sociology and anthropology of Islam, arousing vigorous conceptual and methodological dialectics in scholarship. Without centralizing the conceptual problematic in the first place, and without being confined to the preceding theoretical struggles, Kamaludeen Mohamed Nasir’s Representing Islam: Hip-Hop of the September 11 Generation, a cultural and social hermeneutic of the synthesis between Islamic religiosity and hip-hop culture as practiced and perceived by Muslim youth around the world, nevertheless provides interesting answers, in both conceptual and empirical forms, to these primordial questions. It sheds new light on understanding and interpreting the articulation, manifestations, and implications of and about Islam in this globalized and digitalized age.